Risks and risk mitigation in homecare for people with dementia—A two‐sided matter: A systematic review. (15th June 2022) - Backhouse, Tamara; Ruston, Annmarie; Killett, Anne; Ward, Renée; Rose‐Hunt, Julia; Mioshi, Eneida
Abstract: Policy guidance promotes supporting people to live in their own homes for as long as possible with support from homecare services. People living with dementia who need such support can experience a range of physical and cognitive difficulties, which can increase the risks associated with homecare for this group. We aimed to examine risk and safety issues for people with dementia and their homecare workers and risk mitigation practices adopted by homecare workers to address identified risks. We searched MEDLINE, EMBASE, AMED, CINAHL, PsycINFO, ASSIA and Cochrane Central Register of Controlled Trials databases 5 March 2021. Included studies focussed on homecare for people with dementia and had a risk or safety feature reported. Risk of bias was assessed with the Joanna Briggs Institute Critical Appraisal tools. Two authors assessed articles for potential eligibility and quality. A narrative synthesis combines the findings. The search identified 2259 records; 27 articles, relating to 21 studies, met the eligibility criteria. The review identified first‐order risks that homecare workers in the studies sought to address. Two types of risk mitigation actions were reported: harmful interventions and beneficial interventions. Actions adopted to reduce risks produced intended benefits but also unintended consequences, creating second‐order risks to both clients with dementia and homecare workers, placing them at greater risk. Risk mitigation interventions should be person‐centred, the responsibility of all relevant professions, and planned to minimise the creation of unintended risks.